2021
DOI: 10.1080/26395916.2021.1939789
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale agricultural investments in Eastern Africa: consequences for small-scale farmers and the environment

Abstract: Available empirical evidence about the impacts of large-scale agricultural investments (LAIs) in low-income countries is skewed towards the assessment of economic benefits. How LAIs affect land use and the environment is less understood. This study assesses how small-scale farmers living close to an LAI perceive the changes LAI's inflict on land use, land management, and tree cover in Kenya, Mozambique, and Madagascar. It also investigates their perceptions regarding LAI's impacts on the general environment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Besides population dynamics, macroeconomic forces such as large-scale land acquisition (LSLA) are considered a major non-demographic driver of deforestation (e.g., Rudel et al 2009, Magliocca et al 2020 and can add substantial pressure on the local natural resource base and consequently on natural resource-dependent livelihoods at forest frontiers (Cotula 2012, Carter et al 2017). Moreover, it has been shown that LSLA affects the land use of surrounding smallholders and thus indirectly contributes to deforestation, for which migrants are often blamed (Zaehringer et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Besides population dynamics, macroeconomic forces such as large-scale land acquisition (LSLA) are considered a major non-demographic driver of deforestation (e.g., Rudel et al 2009, Magliocca et al 2020 and can add substantial pressure on the local natural resource base and consequently on natural resource-dependent livelihoods at forest frontiers (Cotula 2012, Carter et al 2017). Moreover, it has been shown that LSLA affects the land use of surrounding smallholders and thus indirectly contributes to deforestation, for which migrants are often blamed (Zaehringer et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…En la misma línea de ideas, Langemeyer et al (2021) observa que aunque la agricultura urbana es una solución ideal que permitiría reducir los impactos ambientales; la planificación urbana de las ciudades aún no toma en cuenta esta solución. Y más preocupante aún, en algunas zonas del mundo como en África Oriental, se observa que la agricultura industrial origina deforestación, impactando directamente en el uso de la tierra y el medio ambiente, y afectando a los pequeños agricultores (Zaehringer et al, 2021). También es Estados Unidos y en Sri Lanka se observa alarmantes informes sobre la contaminación del agua.…”
Section: Introductionunclassified